Dynamic bimorph thermo-piezoelectric benders with arbitrary support location. Part II: Application to energy harvesting-numerical results and discussions - Gevorg Y. Bagdasaryan; Armanj D. Hasanyan; Davresh J. Hasanyan (National Academy of Sciences of Armenia)
A comprehensive theoretical analysis of a dynamic thermo-ferro-electric pre-stressed bimorph energy harvester is performed. The analysis also takes into account pyroelectric and thermal expansion effects. The most general analytical expression for the energy conversation coefficients are presented for bi-layer. These coefficients we derive for more general situation when mechanical, electrical, thermal fields are present. We derive coefficients (transformation coefficients) for sensing, actuating, and energy harvesting. As a particular case, we derive an analytical expression for the energy harvesting coefficient due to pyroelectric and thermal expansion effects in a rater general situation. This is a function of material properties, location of boundary conditions, vibration frequency, and in plane compressive/tensile follower force. Numerical simulations of the analytical results are presented. Effects of volume fraction, material properties, applied mechanical loads, and boundary conditions on the harvesting coefficients are introduced in the figures. The results for a cantilever and a simply-supported plate-layer are obtained as particular cases. The result for a low frequency (static) system is obtained as a particular case by approaching the vibration frequency to zero. It is shown that volume fraction, material properties, plain compressive/tensile follower force, the location of the boundary conditions, and the vibrational frequency of the bimorph strongly influence the strain distribution, and this in effect influences the charge coefficient and the generation of energy. The proposed model can be extended to thermal energy harvesters of piezoelectric-shape memory alloy (SMA) composites. Применение к накоплению энергии – численные результаты и обсуждение. Приводится численный анализ задачи, рассмотренной в предыдущем номере журнала, для частных примеров консольной и шарнирно опёртой балок. Էներգիայի կուտակում – թվային հետազոտություն և քննարկում Ամսագրի նախորդ համարում դիտարկված խնդրի համար բերված են թվային արդյունքներ մասնավորապես կոնսոլային և հոդակապորեն ամրակցված հեծանների համար:
Keywords: Physics; Mechanics of deformable solids